One-pot synthesis of dicyclopenta-fused peropyrene via a fourfold alkyne annulation - Ma, Ji; Fu, Yubin; Liu, Junzhi; Feng, Xinliang (Beilstein Journal of Organic Chemistry, 2020)
A novel dicyclopenta-fused peropyrene derivative 1 was synthesized via a palladium-catalyzed four-fold alkyne annulation of 1,3,6,8-tetrabromo-2,7-diphenylpyrene (5) with diphenylacetylene. The annulative π-extension reaction toward 1 involved a twofold [3 + 2] cyclopentannulation and subsequent twofold [4 + 2] benzannulation. The structure of 1 is unambiguously confirmed by X-ray crystallography; 1 adopted a twisted geometry due to the steric hindrance of the phenyl rings and the hydrogen substituents at the bay regions. Notably, compound 1 exhibits a narrow energy gap (1.78 eV) and a lower LUMO energy level than the parent peropyrene without the fusion of the five-membered rings. In addition, the effects of the peri-fused pentagons on the aromaticity and molecular orbitals of 1 were evaluated by theoretical calculations. This work presents an efficient method to develop π-extended aromatic hydrocarbons with cyclopenta moieties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Alkyne annulation; Cyclopenta-fused polycyclic aromatic hydrocarbons; Nonplanarity; Peropyrene; Regioselectivity